Comparing different techniques of uterine artery occlusion during laparoscopic myomectomy: a randomized controlled trial - Ahmed Shoukry; Omar Ashraf Aboali; Manar Fayez Abdelquader; Ahmed M.H. Gouda (BMC Women's Health, 2026)
Abstract Background Laparoscopic myomectomy carries a risk of significant intraoperative bleeding. Although uterine artery occlusion is used to reduce blood loss, its overall benefit compared with no occlusion and the relative performance of different occlusion techniques remain uncertain. This study primarily compared uterine artery occlusion, performed using different techniques, versus no occlusion during laparoscopic myomectomy, and secondarily explored the feasibility, safety, operative outcomes, and short-term ovarian reserve outcomes of temporary clipping, shoelace suture, and permanent bipolar coagulation. Methods This prospective, single-blind, four-arm randomized controlled trial was conducted in Egypt. Of 61 randomized participants with symptomatic uterine leiomyomas, 60 received their allocated intervention and were included in the modified intention-to-treat analysis. Participants were assigned using an intended 1:1:1:1 allocation ratio. The final analyzed groups were uterine artery clipping ( n = 15), shoelace suture ( n = 15), bipolar coagulation ( n = 16), and no occlusion (control; n = 14). The prespecified primary analysis compared uterine artery occlusion performed using different techniques versus no occlusion for estimated intraoperative blood loss and 24-hour haemoglobin decline. Secondary analyses included exploratory four-group comparisons of estimated blood loss, haemoglobin decline, operative time, and transfusion requirement, together with postoperative ovarian reserve markers—anti-Müllerian hormone and antral follicle count—assessed three months after surgery. Results In the prespecified primary comparison, uterine artery occlusion performed using different techniques did not produce a detectable reduction in estimated intraoperative blood loss compared with no occlusion (median 260 mL [IQR 160–400] vs. 205 mL [IQR 190–300]; Hodges–Lehmann estimated difference 30 mL, 95% CI − 50 to 110; p = 0.416). Mean 24-hour haemoglobin decline was also similar between groups (1.17 ± 0.78 vs. 1.11 ± 0.44 g/dL; p = 0.759; Cohen’s d = 0.07). Operative time was longer with uterine artery occlusion (median 160 vs. 120 min; p = 0.007). Blood transfusion was required in 11 of 46 participants (23.9%) in the occlusion group and none of 14 participants in the no-occlusion group (risk difference 23.9% points, 95% CI 0.2–37.9; Fisher’s exact p = 0.053). In secondary exploratory four-group analyses, estimated blood loss differed among techniques. Bipolar coagulation had the lowest observed median blood loss and the shortest operative time among the occlusion techniques; however, superiority over no occlusion was not established. At three months, no detectable between-group differences in postoperative anti-Müllerian hormone or antral follicle count were detected after adjustment for the corresponding baseline values and age. Conclusions In this trial, uterine artery occlusion performed using different techniques did not produce a detectable reduction in estimated intraoperative blood loss or 24-hour haemoglobin decline compared with no occlusion and was associated with longer operative time. Transfusions occurred only in the occlusion group, although the pooled comparison did not reach statistical significance. Because the observed variability in blood loss substantially exceeded the a priori assumption, the primary comparison was underpowered and remained compatible with clinically important benefit or harm. The exploratory technique-specific findings were method-dependent and did not establish the superiority of any individual occlusion technique. No detectable short-term between-group difference in ovarian reserve markers was observed after adjustment for baseline imbalances. Trial registration ClinicalTrials.gov Identifier: NCT07352761. Study first submitted: 21 December 2025; study first posted: 20 January 2026. The trial was retrospectively registered.